2021
DOI: 10.1161/circheartfailure.120.008170
|View full text |Cite
|
Sign up to set email alerts
|

NAD + Redox Imbalance in the Heart Exacerbates Diabetic Cardiomyopathy

Abstract: Background: Diabetes is a risk factor for heart failure and promotes cardiac dysfunction. Diabetic tissues are associated with nicotinamide adenine dinucleotide (NAD + ) redox imbalance; however, the hypothesis that NAD + redox imbalance causes diabetic cardiomyopathy has not been tested. This investigation used mouse models with altered NAD + redox balance to test this hypothesis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 49 publications
(91 reference statements)
1
24
0
Order By: Relevance
“…Our study found notable effects on both NAD + and mitochondrial respiration/abundance in myocardial tissue, suggesting a comprehensive positive effect of light-phase prednisone on aerobic energy production in heart. Moreover, the effects of light-phase prednisone on Nampt upregulation and NAD + biogenesis in heart are consistent with the positive effects of NAD + replenishment in heart failure [ 19 , 44 , 45 , 51 ]. However, our study was performed in male mice and additional studies are required to address whether effect size and mechanisms are replicable in female mice.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our study found notable effects on both NAD + and mitochondrial respiration/abundance in myocardial tissue, suggesting a comprehensive positive effect of light-phase prednisone on aerobic energy production in heart. Moreover, the effects of light-phase prednisone on Nampt upregulation and NAD + biogenesis in heart are consistent with the positive effects of NAD + replenishment in heart failure [ 19 , 44 , 45 , 51 ]. However, our study was performed in male mice and additional studies are required to address whether effect size and mechanisms are replicable in female mice.…”
Section: Discussionsupporting
confidence: 63%
“…Perhaps of importance for cardiac metabolism, here we found that the NAD + increase induced by light-phase prednisone treatments correlated with decreased ROS production in normal and infarcted myocardium. Several reports have recently focused on direct effects of NAD + redox state on oxidative stress in conditions of diabetic heart failure [ 44 , 45 ]. Our data cannot discriminate between NAD + repletion versus mitochondrial rescue as main promoter of ROS decrease downstream of light-phase prednisone, and dedicated studies will likely shed light on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our data appear to resolve some mysteries that have persisted in the study of LS. In particular: 1) Why is there a general sparing of some tissues with high energy requirements, as in cardiac-specific Ndufs4 (KO) in the absence of a stressor ( 60 62 )? If disease sequelae are mediated by immune responses, tissue energetics may not play a direct role.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have claimed that there is NAD + /NADH redox imbalance in the diabetic pancreas and lungs. 32,33 After treatment with CCFE, the NAD + /NADH ratio in the CCFE-M and CCFE-H groups significantly increased ( p < 0.05) compared with that in the DM control group, which confirmed that the NAD + /NADH redox imbalance in the pancreas of T2DM rats was alleviated by CCFE. Moreover, Ogura et al 34 found that apigenin increased the intracellular NAD + /NADH ratio in the kidneys of diabetic rats by inhibiting the CD38 activity.…”
Section: Resultsmentioning
confidence: 67%